Assessment Tool for Building Materials - The Role of the Odor. (November 2015) - Vasconcelos, Silvia de Lima; Alho, Carlos; Zeidler, Olaf; Müller, Birgit
Abstract: A parameter for "odor intensity" is integrated into an assessment tool for relative sustainability degree of building materials (PhD work of the author). The investigation tries to figure out if the rating is modified by the inclusion of this parameter and verifies if a building material which is considered sustainable could have a negative odor review. The case study compares three different interior plasters which will be analyzed and compared to a standard solution: cement (REF); gypsum (A), clay (B) and lime (C).